Pengembangan E-Modul Berbasis Software FlipBook maker Materi Peninggalan Megalitik Di Pasemah Dalam Mata Kuliah Sejarah Indonesia Kuno Di FKIP Universitas Sriwijaya - Susanti, L.R. Retno (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This scientific work titled E-modules Development Software-based FlipBook maker megalithic relics in Pasemah in the course of ancient Indonesian history in FKIP Sriwijaya University. Development research uses ALESSI and Trollip development models consisting of three stages, namely planning stage, design stage and development stage. Next after going through the planning, design and development phases, the researchers conducted an alpha test of E-module Software-based FlipBook Maker to the material experts, learning design experts, and media experts with declared valid and decent results Piloted. The practicality of E-module based on Flipbookmaker Software is obtained based on the results of beta test of 3 (three) students with a percentage of 89.0, 96.0, and 94.55 which means to be in a very practical category. The effectiveness of E-module Software based FlipBook Maker is obtained from the results of the field trials, there was an increase in student learning outcomes with the acquisition of the N-gain score of 0.76 with high category. Based on the results of this study it can be concluded that the E-module Software based flipbook maker on megalithic relics in Pasemah in ancient Indonesia history courses developed proved valid, practical, and effective to use In learning.